MODEL PEMBELAJARAN INSIDE OUTSIDE CIRCLE DALAM MENINGKATKAN HASIL BELAJAR SISWA SMA NEGERI 7 AMBON - Rina Juliana Sahuleka; Ali Awan; Stevin Melay (Program Studi Pendidikan Biologi FKIP Unpatti, 2020)
Background: Learning is a process of interaction between teachers and students that is shown to make changes in students' attitudes and mindsets to achieve optimal learning outcomes. The teacher designs learning biology using a contextual approach that is confusing and time-consuming. In learning biology student success is determined by the final outcome of learning. Methods: The subjects in this study were class XI Science 2 and the data obtained by observation, interviews and learning outcomes tests were analyzed descriptively using a list of initial and final test scores. Results: The cognitive aspects of the assessment there were 11 students who scored at intervals (80-100) with a percentage of 68.75% very good information and 5 students who scored at intervals (66-79) with a percentage of 31.25% good information. Evaluation of affective aspects obtained a percentage of 100%. For the Final Test, there are 12 students who score at intervals (80-100), with a percentage of 75% and very good information, and 4 students who score at intervals (66-79), with a percentage of 25% and good information. At the final grade there are 16 students who score at intervals (80-100), with a percentage of 100% and with very good information. Conclusion: The application of the Inside Outside Circle (IOC) type of cooperative learning model to the concept of the human excretion system can improve student learning outcomes by achieving KKM 70.